STRATEGI GURU DALAM MEMBENTUK KARAKTER SISWA DI MADRASAH IBTIDAIYAH BUSTANUL ULUM KOTA BATU - Nuranti Nuranti; Muhammad Hanief; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstractA problem with that reserch is low of character of students on Islamic elementary schools and how the teacher's strategy in forming the character of students in Ibtidaiyah Madrasah, as well as supporting and inhibiting factors in the formation of student character in Ibtidaiyah Madrasas. This research was carried out at the Bustanul Ulum Ibtidaiyah Madrasa in Batu City. The approach in research is qualitaive with a type of case study research, the presence of researcher in the field as a main instrument in colecting data, research data sources are divided into two: primary data and secondary data, data collection researchers use observation, interviews and documentation, analysis techniques The data use of data reductioon, data presentattion and conlusion drawing, cheking and validitty of the data in study include: credibilty,tranferability, pendability with confirmability. A result of this study the character in students include: honest, disciplined, responsible and caring for the environment, the teacher's strategy in forming character through habituation in the classroom and outside the classroom in the form of discussion, giving examples, Dhuha prayer and midnight prayer in congregation, supporting factors in character formation is the teacher's parent and competent inhibiting factor in character building, namely diversity and the parents' sense of indifference towards their child's character.Keywords: Teacher Strategy, Forming, Student Character